On a Dirichlet series connected to a periodic Hurwitz zeta-function with transcendental and rational parameter - Balčiūnas, Aidas; Laurinčikas, Antanas; Stoncelis, Mindaugas (Mathematical Modelling and Analysis, 2023)
In the paper, we construct an absolutely convergent Dirichlet series which in the mean is close to the periodic Hurwitz zeta-function, and has the universality property on the approximation of a wide class of analytic functions.